Struktur komunitas makrozoobentos di Perairan Pesisir Tangerang, Banten - Asep Sahidin; Isdradjad Setyobudiandi; Yusli Wardiatno (Depik, 2014)
The purpose of this study was to determine distribution and abundance macrozoobenthos at Tangerang coastal waters, Banten. Study was carried out from April to August 2013 at Tangerang coastal waters, Banten with purposive sampling method and similarity Bray Curtis analysis using minitab.v15.1.2-Equinox softwere. A total of 5458 individuals macrozoobenthos were recorded during the study, its were belonging to 74 species The abundances of macrozoobenthos at Tanjung Pasir location was 634 ind/m2 dominated by Tellina palatum and Tellina timorensis, Kronjo location was 595 ind/m2 dominated by Codakia puncata and lower macrozoobenthos Cituis location was 177 ind/m2 dominated by Clitellio arenarius and Codakia puncata. The spatial distributin based on similarity Bray-Curtis analysis showed that the Kronjo, Cituis, and Tanjung Pasir locations generate four, three, and five groups, respectively. Nuculana bicuspidata dan Ophryotrocha puerilis was a cosmopolite macrozoobenthos were found at all locations. Generaly, the macrozoobenthos distribution at Tangerang coastal waters were strongly depended on the types of sedimen and dissolved oxygen concentration